UNICEF'S ROLE IN SUPPORTING EFFORTS TO FULFILL THE RIGHTS OF CHILDREN IN INDONESIA IN EDUCATION ACCORDING TO GOAL 4 SDGS 2016-2019 - indrasawitri, gustiayu made; Resen, Putu Titah Kawitri; Kumala Dewi, Putu Ratih (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
This study aims to analyze the role of international organizations mandated to ensure child welfare through a study on the role of UNICEF in promoting the fulfillment of children's rights in Indonesia accordance to the goals of the 4 SDGs. This research is a qualitative descriptive research that uses data collection techniques through library research. This reseach use conseptual basis, namely the role and function of international organizations, the power of international organizations, and the role of international organizations in the field of education. to frame the analysis of the topics raised. This study found that UNICEF as an international organization that plays roles as an actor through their function as norms, socializations, informations and operations. This research examines the moral authority and informational functions of UNICEF, which are manifested through UNICEF's entry into Indonesia to fulfill its mandate and its involvement in developing programs related to optimizing the achievement of SDGs. As a result, the role played by UNICEF can contribute to assisting Indonesia in meeting SDG Goal 4. UNICEF as an actor can support Indonesia in fulfilling the goals of the 4 SDGs through the norms function by making CPAP. Socializations function by holding inclusive education campaigns.The information function is the creation of a baseline as well as the operations function which is realized into several programs such as the literacy improvement program, the roots program and PAUD HI.